MENINGKATKAN KETERAMPILAN SOSIAL MELALUI PERMAINAN TRADISIONAL JAMURAN PADA ANAK USIA 5-6 TAHUN DI TAMAN KANAK-KANAK PERTIWI DHARMA WANITA PERSATUAN SETDA PROVINSI RIAU - Selviana, Mery; Chairilsyah, Daviq; Risma, Devi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The purpose of the research is as follows: 1) To know the social skills of children through traditional games of mushroom in children aged 5-6 years in TK Pertiwi Dharma Wanita Persatuan Setda Province of Riau. 2) To know the application of traditional game of mushroom in order to increase social skill of children in children aged 5-6 years in TK Pertiwi Dharma Wanita Persatuan Setda Province of Riau. 3) To find out the magnitude of social skills improvement of children through the traditional game of mushrooms in children aged 5-6 years in TK Pertiwi Dharma Wanita Persatuan Setda Province of Riau. This form of research is collaborative classroom action research. The data collected used is the research instrument using observation sheet consisting of 4 indicators of social skills of children. Based on the result of research indicate in every cycle of meeting there is improvement that can be seen through result of percentage of social skill of children, with percentage value before action cycle 40,33%, cycle I 45,44% and cycle II 79,48%. It can be seen from the data of the upgrading from before the treatment to cycle I of 12,67% and cycle I to cycle II increase that happened equal to 74,91% and increase from before treatment to cycle II equal to 97,07%. So it can be concluded that traditional game of mushroom can improve social skill of children aged 5-6 years in Kindergarten Pertiwi Dharma Wanita Persatuan Setda Province of Riau in accordance with hope done in this research.Keywords: Social Skills, Traditional Game Of Mushrooms